Implementation of Academic Supervision on the Professional Dimension of Teachers on Teacher Performance at State Elementary School 147 Palembang - Sari, Karlina; Widayatsi, Tri; Mulyadi, Mulyadi (Journal of English Language and Education, 2026)
This study aims to find out and describe the implementation of academic supervision in the professional dimension of teachers on teacher performance at SD Negeri 147 Palembang which includes aspects of planning, implementation, supervision, problems, and solutions implemented. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation, then analyzed systematically. The results of the study show that the implementation of academic supervision carried out by the principal has gone well and in accordance with the expected goals through the stages of planning, implementation, and structured supervision. However, there are still several problems, such as the preparation of supervision schedules that are not optimal, the lack of pedagogic competence of teachers, difficulties in designing learning tools according to student needs, the limited ability of teachers to operate digital devices, and the lack of reflection activities at the end of learning. To overcome these problems, there is an increase in socialization and training for teachers, a strengthening of collaboration between schools and parents, and the development of more innovative and student-centered learning strategies and methods, so that teachers are expected to continue to develop as professional educators who are able to answer the challenges of 21st century education.